PROBLEMATIKA GURU DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN BERBASIS DIGITAL DI MIN 1 BUNGO - Ahmad Farhan Alisnaini; Rika Novita; Syofiani; Rieke Alyusfitri (STKIP Subang, 2026)
The development of digital technology has brought significant changes to the world of education, including at the madrasah ibtidaiyah level. The implementation of digital-based learning has become one of the strategic efforts to improve the quality of learning, but in practice, it still faces various challenges at the teacher level. This study aims to describe and analyze the problems faced by teachers in implementing digital-based learning at MIN 1 Bungo. This study uses a qualitative approach with a case study research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies involving teachers and madrasah management. Data analysis was carried out through the stages of data reduction, data presentation, and continuous conclusion drawing. The results of the study show that the problems faced by teachers in digital-based learning include limited digital pedagogical competence, unpreparedness in designing interactive digital learning, limited supporting facilities and infrastructure, and resistance to changes in the learning paradigm. In addition, the lack of optimal policy support and teacher professional development programs also affects the effectiveness of digital-based learning implementation. However, this study also found good practices that show the great potential of digital learning when supported by teacher competence, adequate facilities, and a school culture that is adaptive to innovation. The conclusion of this study emphasizes that the implementation of digital-based learning in madrasah ibtidaiyah requires a comprehensive and sustainable approach, not only focusing on the provision of technology, but also on strengthening teacher competencies, institutional support, and the integration of educational values. The findings of this study are expected to serve as a reference for policy makers and education practitioners in developing contextual digital learning strategies oriented towards improving the quality of learning.